PENYEBAB PERCERAIAN DALAM KELUARGA DI KOTA PALU - Fatmawati, Fatmawati; Kasmiati, Kasmiati (Musawa: Journal for Gender Studies, 2021)
Divorce is a result of the inability of husband and wife to overcome problems in the household. Based on data from the Palu City Ahama Court, husband and wife’s opinion occurred a lot in palu city. For this reason, this study aims to explain the causes of husband and wife divorce in Palu City. Through field research by reviewing and analyzing data from interviews, observations, and dolumentation, qualitative analysis can be done. From the results of the analysis, it was found that the phenomenon of the cause of divorce in Palu City in terms of internal in the household environment occurred because one party left the obligation to make a living for the survival of the family with a percentage of 45.38%, the occurrence of moral crises such as gambling, drunkenness with a percentage of 6.62%, excessive jealousy that caused heartache with a percentage of 3.01%, Disputes that occur continuously with a percentage of 29.51%, unhealthy polygamy 1.80%. Furthermore, another cause of divorce in Palu City is in terms of external factors, is because parents who interfere too much in household affairs with a percentage of 8.20%, other parties as third parties by spreading slander whose percentage reaches 2.40%.